Normative talk about talk in child-caregiver interaction in Mexican families - Rojas-Nieto Cecilia (Psychology of Language and Communication)
This article shares the current interest in characterizing family interaction with children in different communities. I have investigated one aspect of possible diversity that is rarely reported: the normative discourse that caregivers direct towards children’s interventions that deviate from coding conventions, interactional commitments, or pragmatic expectations. Data collected from spontaneous conversations between young children and their caregivers in middle-class urban families in the Mexican highlands show that the motives for normative control in this community are very diverse. The most prominent normative targets relate to lexical conventionality and phonetic faithfulness, paying and showing attention to interlocutors, providing contingent interventions (especially answering questions), and making polite requests. Taken together, caregivers’ normative interventions touch on aspects of the interactional foundations of language, the adequacy of meaning and form for intercomprehension and the social rituals of politeness.